Unreplicated factorial experimental designs for offline quality improvement and industrial process optimisation. (3rd February 2023) - Farhoud, Hager; Taleb, Lotfi
A problem frequently encountered in the industrial offline improvement of quality is to identify from among many factors, those which are responsible for large changes in the quality characteristics, namely factors with active location and/or dispersion effects. Unreplicated experimental designs propose economic tools to discover what manufacturing conditions minimise product variation, maintain product measurements near the desired target value and make the product insensitive to environmental changes. However, no degrees of freedom are left to estimate the experimental error. To remove this dependency structure of residuals at the high and low levels of factor combinations, this study first addresses a synthesis and a critical analysis of existing location and dispersion effect identification methods. Second, a new method is proposed, and robustness check is based on real example and extensive simulation study. Third, practical issues are presented to enlighten investigators in their decision-making process.